FINANCIAL DEVELOPMENT AND SAVINGS: EMPIRICAL EVIDENCE FROM NIGERIA - OSUJI, OBINNA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
The study examined the nexus between Financial Development and savings in Nigeria for the period 1981 to 2018. The data for the study was sourced from Central Bank of Nigeria (CBN) Statistical Bulletin covering 37 years and was analyzed using Ordinary Least Square (OLS) econometric technique and Granger Causality test. The study found that Financial Development had a positive significant relationship with savings in Nigeria while savings rate on the other hand had a positive but insignificant effect on savings. Furthermore, the result of the Granger causality test indicated there is a unidirectional causality running from financial development to Savings in Nigeria. The study, therefore, recommended for greater deepening of the financial sector through financial innovations, improved financial instruments and increased deposit rates so as to enable the sector to further contribute to domestic savings mobilization in Nigeria.